2020
DOI: 10.29333/iejme/7994
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Students’ Performance in Mathematics in Tanzania: The Teacher’s Perspective

Abstract: One of the aims of teaching and learning mathematics is to encourage and enable learners to become confident in using mathematics to analyze and solve practical problems in real-life situations. However, while a few students prosper in learning of mathematics, many students find it difficult and ultimately fail the subject. This study analyses students' mathematics performance data and examines the perception of teachers on the causes of poor academic performance in mathematics among students in Tanzania. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 16 publications
(32 reference statements)
3
39
1
Order By: Relevance
“…However, the finding is contradicted by those of Ayeobasan (2019), Oloja and Adeniyi (2019), Oribhabor (2019), Olajumoke and Olajumoke (2018), PISA (OECD, 2010) and Nannyonjo (2007) that gender differences exist while learning mathematics in favor of males. Also, that gender differences exist in students' performance in Mathematics in favour of the females as reported by Mazana, Montero and Casmir (2020) and Jayanthi and Srinivasan (2015).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, the finding is contradicted by those of Ayeobasan (2019), Oloja and Adeniyi (2019), Oribhabor (2019), Olajumoke and Olajumoke (2018), PISA (OECD, 2010) and Nannyonjo (2007) that gender differences exist while learning mathematics in favor of males. Also, that gender differences exist in students' performance in Mathematics in favour of the females as reported by Mazana, Montero and Casmir (2020) and Jayanthi and Srinivasan (2015).…”
Section: Discussionmentioning
confidence: 78%
“…Nannyonjo's (2007) study on grade six pupils indicated that in mathematics boys significantly scored 4 points higher than girls in Uganda National Examination Board National Assessment of Progress in Education. Contrarily, Mazana, Montero and Casmir (2020) analysed students' performance data in mathematics between 2008 and 2016 in Tanzanian schools. The analysis revealed that in the Upper secondary school, girls outperformed boys in many occasions.…”
Section: Introductionmentioning
confidence: 99%
“…It is also regarded as a belief held by individuals that reflects their opinions and feelings and can be sometimes manifested in behaviour. Attitudes, behaviour, and feelings are interrelated in such a way that people's attitudes determine their behaviour towards objects, situations, and people (Mazana, 2020).…”
Section: Attitude Towards Mathematicsmentioning
confidence: 99%
“…Notwithstanding, poor understanding of prerequisite concepts which comes as result of the use of inappropriate teaching methods, poor attitudes and perceptions towards the study of calculus were some of the contributing factors to low performance in calculus (Odell, Cutumisu, & Gierl, 2020;Wang, Hofkens, & Ye, 2020;Mazana, Montero, & Casmir, 2020).…”
Section: Introductionmentioning
confidence: 99%